Concurrent Cemento-Osseous Dysplasia and Osteogenic Sarcoma: Report of Two Cases - A. A. Olusanya; B. F. Adeyemi; A. O. Adisa (Case Reports in Medicine)
Aim. Cemento-osseous dysplasia (COD) represents a rare group of benign fibroosseous disorders, while osteogenic sarcoma (OS) on the hand, is a malignant tumour of ominous prognosis. A combination of COD and OS is rare and sparsely reported in literature. There are only four reported cases known to the authors. The aim of this paper is to report additional cases of COD occurring concurrently with OS. Materials and Methods. The clinicoradiologic findings and histological analysis of mandibular lesions in two patients who reported at the Dental Centre of the University College Hospital, Ibadan, Nigeria, are presented. Results. The two patients were diagnosed of mandible osteosarcoma occurring concurrently with bilateral mandibular focal cemento-osseous dysplasia. Conclusion. The simultaneous occurrence of osteosarcoma and cemento-osseous dysplasia raises the question of whether COD has transformed into OS or a collision tumour has occurred and their simultaneous occurrence is just a coincidence.